2010
DOI: 10.1155/2011/984505
|View full text |Cite
|
Sign up to set email alerts
|

Common Fragile Site Tumor Suppressor Genes and Corresponding MouseModels of Cancer

Abstract: Chromosomal common fragile sites (CFSs) are specific mammalian genomic regions that show an increased frequency of gaps and breaks when cells are exposed to replication stress in vitro. CFSs are also consistently involved in chromosomal abnormalities in vivo related to cancer. Interestingly, several CFSs contain one or more tumor suppressor genes whose structure and function are often affected by chromosomal fragility. The two most active fragile sites in the human genome are FRA3B and FRA16D where the tumor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 83 publications
0
30
0
1
Order By: Relevance
“…In vivo, replication stress has been observed early in the process of tumor development as a result of alteration of replication fork progression and nucleotide deficiency caused by activation of oncogenes (Di Micco et al 2006;Bester et al 2011). In cancer cells, human common fragile sites are hotspots for chromosomal deletions, amplifications, and rearrangements (Burrow et al 2009;Drusco et al 2011; OzeriGalai et al 2011 OzeriGalai et al , 2012, and a large-scale screen of deletions in 746 cancer cell lines reported that many areas of unexplained deletions are in fragile sites (Bignell et al 2010).The alterations at human common fragile sites in cancer cells are proposed to result from the processes of DNA repair at these sites. Homologous recombination repair pathways are stimulated by DNA breaks, single-strand gaps, and stalled replication forks (Symington et al 2014); all of which have been proposed to be present at common fragile sites (Le Tallec et al 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo, replication stress has been observed early in the process of tumor development as a result of alteration of replication fork progression and nucleotide deficiency caused by activation of oncogenes (Di Micco et al 2006;Bester et al 2011). In cancer cells, human common fragile sites are hotspots for chromosomal deletions, amplifications, and rearrangements (Burrow et al 2009;Drusco et al 2011; OzeriGalai et al 2011 OzeriGalai et al , 2012, and a large-scale screen of deletions in 746 cancer cell lines reported that many areas of unexplained deletions are in fragile sites (Bignell et al 2010).The alterations at human common fragile sites in cancer cells are proposed to result from the processes of DNA repair at these sites. Homologous recombination repair pathways are stimulated by DNA breaks, single-strand gaps, and stalled replication forks (Symington et al 2014); all of which have been proposed to be present at common fragile sites (Le Tallec et al 2014).…”
mentioning
confidence: 99%
“…In vivo, replication stress has been observed early in the process of tumor development as a result of alteration of replication fork progression and nucleotide deficiency caused by activation of oncogenes (Di Micco et al 2006;Bester et al 2011). In cancer cells, human common fragile sites are hotspots for chromosomal deletions, amplifications, and rearrangements (Burrow et al 2009;Drusco et al 2011;OzeriGalai et al 2011OzeriGalai et al , 2012, and a large-scale screen of deletions in 746 cancer cell lines reported that many areas of unexplained deletions are in fragile sites (Bignell et al 2010).…”
mentioning
confidence: 99%
“…For example, the FRA3B is embedded within a large tumour suppressor gene, FHIT , that is frequently deleted in lung and breast cancer, as well as other carcinomas [ 62 ]. Although Fhit -/-KO mice exhibited only a marginal increase of tumourigenesis in response to various carcinogens, crossing these mice with other disease models, such as Vhl -/-KO or Nit1 -/-KO animals, rendered full penetrance of tumour development (reviewed in [ 63 ]), suggesting a cooperative role for FHIT during tumourigenesis. Recently, Saldivar et al showed that loss of Fhit expression in precancerous lesions initiates genomic instability that may eventually facilitate malignant transformation, linking alterations at CFSs to the origin of cancer genomic instability [ 64 ].…”
Section: Inactivation Of Tumour Suppressor Genes By Deletionmentioning
confidence: 99%
“…Recently, Saldivar et al showed that loss of Fhit expression in precancerous lesions initiates genomic instability that may eventually facilitate malignant transformation, linking alterations at CFSs to the origin of cancer genomic instability [ 64 ]. Other examples of tumour suppressor gene loss involving CFSs, include WWOX within the FRA16D , PARK2 within the FRA6E, and CAV1 and TES within the FRA7K [ 63 ].…”
Section: Inactivation Of Tumour Suppressor Genes By Deletionmentioning
confidence: 99%
“…All CFSs investigated at molecular level up to now contain protein-coding genes, most of which extend over hundreds of kilobases of DNA (Smith et al, 2007). The FHIT and WWOX genes encompassing FRA3B and FRA16D, respectively, are both > 1 Mb in length and have been shown to exhibit tumor suppressor activity in vivo and in vitro (Drusco et al, 2011;Lewandowska et al, 2009;Saldivar et al, 2010). There are many reports of deletions within CFSs harboring these genes (McAvoy et al, 2007).…”
Section: General Featuresmentioning
confidence: 99%